A simple square-rooting circuits using available commercial devices - Sakul, Chaiwat; Chaisayun, Ittipong (Thailand Electrical Engineering Journal (TEEJ), 2024)
This paper proposes two square-rooting circuits consisting of AD844 and CD4007. Principle of operation of the proposed circuits is based on the square-law characteristic of MOS transistor within CD4007. The first square root circuit gives the output signal negative. The second circuit works give the output signal positive. Simulation results based on LTspice program agree well with theoretical anticipation.